مشروعية إنشاء الأحزاب السياسية للأقليات الدينية في الإسلام - Kalibi, Yusuf Atiyah; Muhammad Husni, Ahmad; Fakhri, Anwar (Journal of Islamic and Human Advanced Research- JIHAR, 2014)
تناولت هذه الدراسة جانباً مهما من جوانب الحقوق السياسية للأقليات الدينية في الإسلام، وتكمن مشكلة الدراسة حول مدى مشروعية قيام أحزاب سياسية للأقليات الدينية في الدولة الإسلامية، وتهدف الدراسة لبيان مدى سماحة الإسلام وتقبله للآخر، وبيان أن الأساس في تعامل الدولة الإسلامية مع كافة مواطنيها هو المساواة، وانتهجت الدراسة المنهج الإستقرائي لجمع المادة الفقهية، والمنهج التحليلي لتحليل ما ورد من أراء وأدلة والرد عليها، وقد توصلت الدراسة إلى عدة نتائج من أبرزها، إباحة تشكيل أحزاب سياسية للأقليات الدينية في الدولة الإسلامية وفق شروط معينة، إن القول بالإباحة يتفق مع النظرة المقاصدية والمصالحية للشريعة الإسلامية. *********************************************************** This study is an important aspect of political rights for religious minorities in Islam , and the problem is the study about the legality of the political parties of religious minorities in the Islamic state , and the study aims to demonstrate the extent of tolerance of Islam and accepted by the other, and a statement that the basis for the deal of the Islamic state with all of its citizens is equality , and pursued the study inductive approach to collecting material jurisprudence , and the analytical method for the analysis of the statement of views and evidence and respond to them , the study found several results, most notably , the legalization of the formation of political parties, religious minorities in the Islamic state under certain conditions , if say by permissible consistent with the outlook Makassed and Almsalehih Islamic law.